Nicotine Dependence, Perceived Behavioral Control, Descriptive Quitting Norms, and Intentions to Quit Smoking among Chinese Male Regular Smokers. (2nd January 2021) - Chen, Haide; Zhao, Boqiang; Li, Xinwei; Xie, Ruibo; Li, Weijian
Abstract: Background : The association between nicotine dependence and intentions to quit smoking is well established. However, the underlying mechanisms and psychosocial factors that moderate this relationship have not been adequately delineated. Reinforcement theory, social learning theory, the theory of planned behavior, and the focus theory of normative conduct suggest that perceived behavioral control (PBC) over smoking cessation is a central mechanism that underlies the relationship between nicotine dependence and quitting intentions. Purpose/Objectives: The present study tested a moderated mediation model to examine the roles of PBC over smoking cessation and social norms, in the relationship between nicotine dependence and quit intentions among male regular smokers. Methods: Self-report measures of nicotine dependence, PBC over smoking cessation, descriptive and injunctive quitting norms, and intentions to quit smoking were administered to 204 Chinese male regular smokers. Results: Nicotine dependence was negatively related to quit intentions, and this relationship was mediated by PBC over smoking cessation. Further, the relationship between nicotine dependence and PBC was moderated by descriptive rather than injunctive quitting norms. The negative effects of nicotine dependence on PBC over smoking cessation were not significant among male regular smokers who reported strong descriptive quitting norms. Conclusions/Importance: Poor PBC over smoking cessation underlies the negative effects of nicotine dependence, and descriptive quitting norms act as a buffer against the adverse effects of nicotine dependence on PBC over smoking cessation. These findings have implications for smoking cessation interventions for male regular smokers.